Como resolver:
4(x+1) - (x-4)(x+4)=4x
Soluções para a tarefa
Respondido por
9
4(x+1) - (x-4)(x+4)=4x
4x + 4 - (x² + 4x - 4x - 16) = 4x
4x + 4 - x² - 4x + 4x + 16 = 4x
- x² + 4x + 4x - 4x - 4x + 16 = 0
- x² + 8x - 8x + 16 = 0 cancela + 8x - 8x
- x² + 16 = 0
- x² = - 16.(-1)
x² = 16
x = ± √16
x = ± 4
S[- 4 , + 4]
4x + 4 - (x² + 4x - 4x - 16) = 4x
4x + 4 - x² - 4x + 4x + 16 = 4x
- x² + 4x + 4x - 4x - 4x + 16 = 0
- x² + 8x - 8x + 16 = 0 cancela + 8x - 8x
- x² + 16 = 0
- x² = - 16.(-1)
x² = 16
x = ± √16
x = ± 4
S[- 4 , + 4]
Respondido por
5
Olá. Temos isso:
4 ( x +1) - ( x - 4).(x+4) = 4 x
4 x + 4 - x² + 4 x - 4 x - 16 = 4 x
- x ² + 4 x - 12 = 4 x
- x² + 4 x - 12 - 4x = 0
- x² -12 = 0
- x² = 12
- x =![\sqrt{12} \sqrt{12}](https://tex.z-dn.net/?f=+%5Csqrt%7B12%7D+)
- x =
x(-1)
x = -![-2\sqrt{3} -2\sqrt{3}](https://tex.z-dn.net/?f=+-2%5Csqrt%7B3%7D+)
Espero ter ajudado.
;)
4 ( x +1) - ( x - 4).(x+4) = 4 x
4 x + 4 - x² + 4 x - 4 x - 16 = 4 x
- x ² + 4 x - 12 = 4 x
- x² + 4 x - 12 - 4x = 0
- x² -12 = 0
- x² = 12
- x =
- x =
x = -
Espero ter ajudado.
Perguntas interessantes